THE EFFECT OF THE THINK PAIR SHARE LEARNING MODEL ON STUDENTS' PROBLEM-SOLVING AND CRITICAL THINKING SKILLS - Agustiani, Sherlia; Sudrajat, Sudrajat (Nindikayla Institute, 2024)
The purpose of this study is to determine the effect of learning models on students' problem-solving abilities and critical thinking skills. This study used a quasi-experimental study with a population of class VIII students. The sampling technique uses purposive sampling. The research design used was Noneequivalent (pretest and posttest) control group design. The data collection technique in this study was a test technique consisting of a pre-test and post-test in the form of a description test of students' problem-solving abilities and critical thinking abilities. The data analysis technique used is descriptive analysis and inferential analysis. Statistical techniques used for descriptive analysis include average, standard deviation, minimum score and maximum score. Meanwhile, to test the research hypothesis using the Hotteling's T2 test and the Independent Sample t-Test. The results of the study are as follows: 1). there is the influence of think pair share learning and scientific learning on problem solving abilities and students' critical thinking skills. 2). learning with think pair share has a greater influence than scientific learning on students' problem-solving abilities and critical thinking skills.